A.S.P.I.R.E: A student led initiative to foster a facilitative environment for undergraduate medical research - Alhad Mulkalwar; Ojas Krishnani; Shirish Rao; Raakhi Tripathi (Perspectives in Clinical Research, 2022)
The uptake of undergraduate research opportunities in India is reported to be disappointing and little is known about the hurdles faced by students in undertaking research activities. As a solution to this issue, a student-led research council named, “A.S.P.I.R.E: Association for Support and Propagation of Innovation, Research and Education,” was formed. Its activities were focused on building a peer-based research environment to learn via module-wise teaching and mentoring sessions, a practical approach to learn evidence-based medicine via journal clubs and maximize the available opportunities via research opportunities database. Research opportunities database is a live dashboard of research projects currently in progress and vacancies therein for undergraduate students, so that they could be a part of the projects in their subjects of interest. Online discussion forums and social media platform were also created to facilitate active discussion and remote learning. 10 peer based teaching sessions and 8 journal clubs have been organized as an outcome of which 46 undergraduate students have undertaken new research activities in a single year. Based on the feedback from both students and faculty members, it can be said that A.S.P.I.R.E, through its systematic and peer-based approach has developed a culture of research and evidence-based medicine among the undergraduate students.